Reflexive intelligence and converging knowledge regimes. Issue 4 (7th June 2021) - de Werd, Peter
ABSTRACT: What is true, or counts as a fact, for whom, under what circumstances, and what are the consequences? This article argues for the need for a reflexive attitude, as the object and subject of knowledge cannot be separated entirely. Intelligence is discussed in terms of a knowledge regime, with various transversal links to other security-related knowledge regimes: judicial and law enforcement, political and policy, news and social media, and science. Various examples illustrate some of the inherent tensions as knowledge flows from one domain to another. However, there are also signs of convergence among these knowledge regimes.